2010
DOI: 10.1245/s10434-010-1399-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Melanoma Antigen-Encoding Gene-1 (MAGE-1) Expression and its Correlation with Poor Prognosis in Differentiated Advanced Gastric Cancer

Abstract: These findings suggest that MAGE-1 protein expression can serve as a predictive marker of poor prognosis in differentiated AGC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
38
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 24 publications
5
38
0
Order By: Relevance
“…Although the expression of cancer-testis antigens in digestive tract malignancies has been studied at the RNA and protein levels, studies evaluating protein expression are mostly limited to MAGEA, NY-ESO-1, and GAGE (25,(27)(28)(29)(30) (27) MAGEA protein expression in two previous studies, similar to our finding of 58% in this study. This finding of more frequent cancer-testis mRNA expression than protein expression has also been observed in other types of cancer (4) and suggests that lowlevel cancer-testis mRNA expression may not translate to biologically significant protein expression.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Although the expression of cancer-testis antigens in digestive tract malignancies has been studied at the RNA and protein levels, studies evaluating protein expression are mostly limited to MAGEA, NY-ESO-1, and GAGE (25,(27)(28)(29)(30) (27) MAGEA protein expression in two previous studies, similar to our finding of 58% in this study. This finding of more frequent cancer-testis mRNA expression than protein expression has also been observed in other types of cancer (4) and suggests that lowlevel cancer-testis mRNA expression may not translate to biologically significant protein expression.…”
Section: Discussionsupporting
confidence: 89%
“…On the other hand, it is difficult to compare these two studies, as Ogata and colleagues (30) only interpreted cases with cytoplasmic staining as MAGEA1-positive based on the debatable notion that MAGEA1 is a cytoplasmic protein (34), whereas Suzuki and colleagues (30) included both positive cytoplasmic and nuclear staining as MAGEA1-positive, which was the more commonly accepted criterion. [Of note, the 6C1 anti-MAGEA antibody that was used in these studies, including ours, in fact detects multiple MAGEA antigens, including MAGEA1, A2, A3, A4, A6, A10, and A12 proteins (31), and to interpret 6C1-positivity, either cytoplasmic and/or nuclear, as MAGEA1 expression (29,30) is in fact misleading.] In our series, we found MAGEA expression in 14% (7 of 50) gastric cancer among all stages, indicating that the true frequency of MAGEA in gastric cancer is likely in the 10% to 15% range.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…However, only a few studies reported the correlation between MAGE gene expression and oncologic outcomes. Ogata et al suggested that MAGE A1 expression can be a predictive maker of poor prognosis in differentiated advanced gastric cancer 21. Gu et al demonstrated that MAGE A9 expression suggests unfavorable survival outcome in hepatocellular carcinoma 22.…”
Section: Discussionmentioning
confidence: 99%